2016
DOI: 10.1007/s12035-016-0235-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA Profiles as Liquid Biopsies for the Characterization and Diagnosis of Fibromyalgia Syndrome

Abstract: This work was aimed at investigating the circulating microRNA (miRNA) profiles in serum and saliva of patients affected by fibromyalgia syndrome (FM), correlating their expression values with clinical and clinimetric parameters and to suggest a mathematical model for the diagnosis of FM. A number of 14 FM patients and sex- and age-matched controls were enrolled in our study. The expression of a panel of 179 miRNAs was evaluated by qPCR. Statistical analyses were performed in order to obtain a mathematical line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 45 publications
0
51
0
1
Order By: Relevance
“…By contrast, the activated "cut and paste" TEs will not be retrotranscribed due to failure of fragmented tRNAs (tsRNAs) to prime [52], preserving genome integrity under a normalscenario (Figure 4). It is therefore hypothesized that an increase in long dsRNA intracellular levels in FM and ME/CFS patients deriving from epigenetic changes, as described [20][21][22][23][24][25][26][27][28][29][30][31]34], could in fact constitute a trigger for the disease in the absence of viral or other type of infection. It is perhaps the particular type of activated elements what drives the individual phenotype towards autoimmunity (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the activated "cut and paste" TEs will not be retrotranscribed due to failure of fragmented tRNAs (tsRNAs) to prime [52], preserving genome integrity under a normalscenario (Figure 4). It is therefore hypothesized that an increase in long dsRNA intracellular levels in FM and ME/CFS patients deriving from epigenetic changes, as described [20][21][22][23][24][25][26][27][28][29][30][31]34], could in fact constitute a trigger for the disease in the absence of viral or other type of infection. It is perhaps the particular type of activated elements what drives the individual phenotype towards autoimmunity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The main affected genes relate to DNA repair, immune system, nervous system & skeletal/organ system development, and chromatin compaction pathways [17,22]. As per miRNA profiling five studies have reported FM miRNomes [23][24][25][26][27], work from our group included.…”
Section: Introductionmentioning
confidence: 99%
“…By reviewing the literature, as described in Methods, we found five studies reporting differential expression (DE) of particular miRNAs in FM patients with respect to healthy population using multiplex approaches, either microarrays or RT-qPCR panels (Table S1 &Table 1). One of them measured miRNA levels in cerebrospinal fluid (CSF) [67], while the rest evaluated them in blood fractions [68][69][70][71]; two used white blood cells [69,71] and two analyzed serum [68,70].…”
Section: Mirnomes Of Fmmentioning
confidence: 99%
“…It must be pointed out that, in an effort to complete the search as much as possible the list of DE miRNAs in FM and ME/CFS used in the SM2miR search not only included the miRNAs listed in Tables 1 & 2 but also those documented in supplementary tables of the listed literature [67][68][69][70][71][72][73][74]. miR-30c ME/CFS ↑(PBMCs) [74] Up-regulated Gil-Zamorano J et al, 2014 [108] miR-143-3p ME/CFS ↑(Plasma) [73] Up-regulated miR-181a-5p ME/CFS ↑(PBMCs) [74] Up-regulated miR-330 ME/CFS ↑(PBMCs) [74] Up-regulated Fluoxetine miR-27b FM ↓(CSF*) [67] Up-regulated Rodrigues AC et al, 2011 [109] ME/CFS ↑( PBMCs) [74] Glucocorticoid miR-16 ME/CFS ↓(Plasma) [73] Up-regulated Rainer J et al, 2009 [110] miR-19b ME/CFS ↑(PBMCs) [74] Up-regulated miR-181a ME/CFS ↑(PBMCs) [74] Up-regulated Rainer J et al, 2009 [110] ; Lu S et al, 2012 [111] miR-223 ME/CFS ↓(NK cells) [72] Up-regulated miR-21 ME/CFS ↓(NK cells) [72] Up-regulated Lu S et al, 2012 [111] miR-10a ME/CFS ↓(NK cells) [72] Up-regulated miR-27a ME/CFS ↑(PBMCs) [74] Up-regulated miR-99b ME/CFS ↑(PBMCs) [74] Up-regulated miR-126 ME/CFS ↓(Plasma) [73] Up-regulated ↑(PBMCs) [74] miR-145 ME/CFS ↑(PBMCs) [74] Up-regulated miR-146a ME/CFS ↓(NK cells) [72] Up-regulated miR-324-5p ME/CFS ↑(PBMCs) [74] Up-regulated miR-339-3p ME/CFS ↑(PBMCs) [74] Up-regulated Morphine miR-16 ME/CFS ↓(Plasma) [73] Up-regulated Dave R.S & Khalili K., 2010…”
Section: Mirna-drug Interactions In Fm and Me/cfsmentioning
confidence: 99%
“…Interestingly, some of these miRs associated to microgravity unloading appear to be deregulated in FM and CFS/ME patients [16,123,18], suggesting that compressive MT may provide a therapeutic effect by restoring miRNA levels.…”
Section: Rationale For Using Mt To Treat Fm and Cfs/me Dysfunctionsmentioning
confidence: 99%